New Insights from Drosophila into the Regulation of EGFR Signaling. - Harden, N. (Methods in molecular biology (Clifton, N.J.), 2017)
Genetic analysis of Egfr signaling in Drosophila has a long-standing track record of making important contributions to our understanding of the Egfr pathway. While the central Ras/MAPK pathway has long been well defined, there is much to learn with regard to its cross talk with other pathways and how it is regulated. A better understanding of the regulation of Egfr signaling is of particular interest with regard to the participation of misregulated Egfr signaling in tumorigenesis. Recent studies in the fly have led to some surprising results, identifying regulators of Egfr acting in unexpected ways.